E-administracja działająca w granicach prawa i godna zaufania. Prawo do prywatności i ochrona danych osobowych jako wyzwanie dla rozwoju e-administracji .......... 45 - Zielińska, Kinga Sabina (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
E-GOVERNMENT ACTING WITHIN THE LIMITS OF THE LAW AND WITH TRUST: THE RIGHT TO PRIVACY AND PROTECTION OF PERSONAL DATA AS A CHALLENGE FOR THE DEVELOPMENT OF E-GOVERNMENTThe dynamic development of e-government, as well as the development of new technologies that can be used in e-government, invariably arouses interest. Citizen data generated within the administration may in future become the object of attacks by entities wishing to gain possession of specific information. Authorities also use processed data not always in the way it should be used. The need to reconcile e-government activities and the right to privacy and the protection of personal data is intrinsically difficult, although – as is clear from already well-established case law – not impossible. This article reflects on possible threats to the right to privacy and the protection of personal data. The author identifies the most significant, in her opinion, threats to these rights arising from the activities of the state and the possibilities of exploiting the dominant position in the citizen-state relationship. The weaker position of the citizen in this relationship enforces the necessity of ensuring appropriate guarantees for the protection of his/her rights and freedoms. Furthermore, the author points out the need to create systems that support e-government in a way that builds citizens’ trust in the state. The guarantor of this trust and efficient e-government, however, is the absolute observance of the principle of legalism, i.e. state authorities acting only on the basis and within the limits of the law. Any other action not only shatters trust in the state, but also opens up the possibility of challenging before international courts the way the state acts. New technologies, which open up new possibilities, may also constitute a temptation for the state to abuse its power in relation to citizens, which is why, in the author’s opinion, the authority competent in matters of personal data protection, which may in the near future also have competences related to the operation of artificial intelligence, plays such an increasingly important role. Only an independent supervisory authority can provide a guarantee for the protection of citizens’ rights and freedoms in a very sensitive area, such as privacy and the possibility of state interference with it.